2007
DOI: 10.1111/j.1744-7917.2007.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical and chemical factors during foraging and culture of the symbiont fungus in Atta sexdens rubropilosa (Hymenoptera: Formicidae)

Abstract: The aim of this paper is to investigate the influence of physical and chemical factors on transport and use of substrate for Atta sexdens rubropilosa workers. Three types of rectangular fragments were used to study the physical influence factors: filter paper with paraffin, filter paper without paraffin and polyester film. To study the chemical factors, some fragments were impregnated with organic extract of orange albedo, others were soaked with soybean oil and for the remaining ones nothing was applied. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…The cutting of the swimwear could be related to the trail‐clearing behavior displayed by leaf‐cutter ants. Also, they are known for collecting inert or unpalatable items, such as paper and plastic, which are later selected inside the nest and discarded as waste . Some Atta species are able to carry more than eight times their weight, such that larger workers may withstand loads over 500 mg .…”
Section: Discussionmentioning
confidence: 99%
“…The cutting of the swimwear could be related to the trail‐clearing behavior displayed by leaf‐cutter ants. Also, they are known for collecting inert or unpalatable items, such as paper and plastic, which are later selected inside the nest and discarded as waste . Some Atta species are able to carry more than eight times their weight, such that larger workers may withstand loads over 500 mg .…”
Section: Discussionmentioning
confidence: 99%
“…Vegetable materials considered unsuitable for fungus cultivation or which may be toxic are rapidly discarded by foragers (Seal & Tschinkel, 2007; Verza et al, 2007). Evidence from the literature indicates that LCA learn to avoid plants unsuitable for the fungus through a feedback mechanism, involving chemical signals (volatiles) from plant fragments of the fungus discarded in the waste (Arenas & Roces, 2016; Green & Kooij, 2018; Römer & Roces, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of leaf-cutting ants have shown that these insects adopt several specific strategies during the collection and processing of leaves [ 63 , 64 ]. In general, they choose leaves based on leaf age [ 65 , 66 ], moisture content [ 67 ], leaf toughness [ 68 ], secondary toxic components [ 69 ], nitrogen content [ 70 ] and vegetative material that is unsuitable for the mutualistic fungus [ 71 , 72 ]. More recently, it has been suggested that endophytic fungi should also be taken into account since there is evidence that the leaf-cutting ants spend more time processing and screening leaves containing certain fungal genera [ 73 ].…”
Section: Discussionmentioning
confidence: 99%